Preparation method of wear-resistant super-hydrophobic coating

By mixing components such as epoxy resin, aminosilane, tetraethyl orthosilicate with metal oxides and carbon nanotubes, and adding fluorosilane to form a sol, the problem of insufficient mechanical wear resistance of the resin-based superhydrophobic coating is solved, and a coating with strong binding force, low wear and superhydrophobic properties is prepared.

CN119505629APending Publication Date: 2025-02-25RESEARCH INSTITUTE OF TSINGHUA UNIVERSITY IN SHENZHEN
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311080228.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the mechanical wear resistance of the resin-based superhydrophobic coating is insufficient and the rolling angle is high, which affects its performance in applications such as anti-icing adhesion, corrosion resistance, self-cleaning, antibacterial and drag reduction.

Method used

By mixing components such as epoxy resin, aminosilane, tetraethyl orthosilicate, and ethanol, adding metal oxides and carbon nanotubes, and finally adding fluorosilane to form an organic-inorganic long-chain integrated sol, and a wear-resistant superhydrophobic coating is obtained by curing.

Benefits of technology

The preparation of a wear-resistant superhydrophobic coating is achieved, with strong coating bonding force and low wear, water contact angle greater than 155°, and water droplet rolling angle less than or equal to 1°, which has good mechanical wear resistance and superhydrophobic properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of a wear-resistant super-hydrophobic coating, which comprises the following steps: carrying out first mixing on epoxy resin, amino silane, tetraethyl orthosilicate and ethanol to obtain a solution; carrying out second mixing on the solution, a metal oxide and a carbon nanotube to obtain a mixed solution; carrying out third mixing on the mixed solution and fluorosilane to obtain sol; and curing the sol to obtain the wear-resistant super-hydrophobic coating. The super-hydrophobic coating obtained through the preparation method of the wear-resistant super-hydrophobic coating has the advantages of being high in body mechanical wear resistance, high in coating binding force and low in abrasion loss, the water contact angle of the prepared super-hydrophobic coating exceeds 155 degrees, and the water drop rolling angle is smaller than or equal to 1 degree.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrophobic coatings, and in particular relates to a method for preparing a wear-resistant super-hydrophobic coating. Background Art

[0002] The surface wettability theory is based on the development of the Young's equation to the Wenzel model, which eventually becomes the Cassie-Baxter model. The super-hydrophobic models of the prior art are all based on the improvement of the Cassie-Baxter model. There are many methods for constructing super-hydrophobic surfaces, including etching modification, laser processing, physical and chemical vapor deposition, electrochemical deposition, polymer layered self-assembly, physical methods such as spraying / dip coating / spin coating / casting. However, all methods of the prior art are constructed using micro-nano structures and modified with low surface energy materials. The mechanical wear resistance of the super-hydrophobic coating caused by the fragile microstructure is insufficient, which is a bottleneck problem recognized by researchers. Moreover, the roll angle of the resin-based super-hydrophobic coating of the prior art is generally high, and the super-hydrophobic surface with a smaller roll angle is conducive to realizing anti-icing adhesion, corrosion resistance, self-cleaning, antibacterial, drag reduction and other engineering applications. The resin-based super-hydrophobic coating of the prior art mainly relies on the new super-hydrophobic surface exposed after wear and tear to be basically the same as the super-hydrophobic surface before wear and tear, and the service life of the super-hydrophobic coating is extended in this way. How to obtain a coating that has both strong wear resistance and good hydrophobicity has become a hot topic in research and development in this field. Summary of the invention

[0003] In view of this, an object of the present invention is to provide a method for preparing a wear-resistant super-hydrophobic coating. The wear-resistant super-hydrophobic coating prepared by the method provided by the present invention has good wear resistance and hydrophobicity.

[0004] The present invention provides a method for preparing a wear-resistant super-hydrophobic coating, comprising:

[0005] The epoxy resin, aminosilane, tetraethyl orthosilicate and ethanol are first mixed to obtain a solution;

[0006] The solution is mixed with metal oxide and carbon nanotubes for a second time to obtain a mixed solution;

[0007] The mixed solution and fluorosilane are mixed for the third time to obtain a sol;

[0008] The sol is solidified to obtain a wear-resistant super-hydrophobic coating.

[0009] In the embodiments of the present invention, there is no particular limitation on the epoxy resin, and any epoxy resin known in the art may be used.

[0010] In the embodiments of the present invention, there is no particular limitation on aminosilane, and aminosilane known in the art may be used.

[0011] In an embodiment of the present invention, the mass ratio of epoxy resin, aminosilane, tetraethyl orthosilicate and ethanol can be selected from 13:10:9:(65-75), and the mass ratio of epoxy resin, aminosilane and tetraethyl orthosilicate must be 13:10:9; the first mixing can be stirred evenly to obtain a transparent solution; the stirring time can be selected from 25-35 minutes, such as 30 minutes.

[0012] In the embodiment of the present invention, the particle size of the metal oxide can be selected from 25 to 35 nm, such as 28 nm, 30 nm, and 32 nm; the metal oxide can be selected from one or more of silicon dioxide, titanium dioxide, and zinc oxide.

[0013] In an embodiment of the present invention, the carbon nanotubes may be selected from modified carbon nanotubes, such as hydroxylated modified carbon nanotubes.

[0014] In an embodiment of the present invention, the mass ratio of metal oxide to carbon nanotubes is selected from 100:3; the amount of metal oxide used can make its concentration in ethanol selected from (0.25-0.4) g / mL, such as 0.3 g / mL, 0.4 g / mL.

[0015] In an embodiment of the present invention, the second mixing may be performed under stirring conditions, and the stirring time may be selected from 25 to 35 minutes, such as 30 minutes.

[0016] In an embodiment of the present invention, the fluorosilane may be selected from all perfluorosilanes, such as perfluorodecyltrimethoxysilane and perfluorodecyltriethoxysilane.

[0017] In an embodiment of the present invention, the amount of fluorosilane added is such that its concentration in ethanol can be selected from 0.1 to 0.2 g / mL, such as 0.15 g / mL.

[0018] In an embodiment of the present invention, the temperature of the third mixing can be selected from 50 to 70°C, such as 55°C, 60°C, and 65°C, and the mixing temperature can be obtained under water bath conditions; the third mixing can be stirring after ultrasound; the ultrasound time is selected from 15 to 25min, such as 18min, 20min, and 23min; the stirring time can be selected from 25 to 40min, such as 30min and 35min; the stirring speed can be not less than 2000rpm, such as 2000rpm and 2500rpm; the obtained sol is an organic-inorganic long chain integrated sol.

[0019] In an embodiment of the present invention, the sol can be coated on the surface of the substrate before curing, and the coating method can be selected from one or more of dipping, spin coating, spraying, roller coating, brushing and pouring. There is no special limitation on the substrate, and those skilled in the art can select substrates of different materials as needed, such as metals, polymer materials and glass products. The metal can be selected from aluminum alloys, and the polymer material can be selected from acrylic boards.

[0020] In an embodiment of the present invention, the curing temperature can be selected from 90 to 110° C., such as 95° C., 100° C., and 105° C.; the curing time can be selected from 0.5 to 1.5 hours, such as 0.8 hours, 1 hour, and 1.2 hours.

[0021] The wear-resistant super-hydrophobic coating provided by the present invention adopts epoxy resin, aminosilane, tetraethyl orthosilicate and ethanol to stir evenly according to a certain mass ratio to obtain a transparent solution; then, metal oxide and hydroxylated carbon nanotubes are added to the solution; finally, fluorosilane is added, and an organic-inorganic long-chain integrated sol is obtained after ultrasonic stirring evenly, and after coating and curing, the wear-resistant super-hydrophobic coating is obtained. The super-hydrophobic coating is formed after the organic-inorganic long-chain integrated sol is cured, and the coating is mechanically wear-resistant in the main body, the coating bonding force is 8.5N, and the wear amount of 240# sandpaper after reciprocating wear for 1.2m with a load of 750g is only 128mg. The method provided by the present invention can be applied to the surfaces of various substrates to prepare the wear-resistant super-hydrophobic coating.

[0022] In the present invention, when the static contact angle is greater than 150° and the rolling angle is less than 10°, the surface is defined as having super-hydrophobic properties. The super-hydrophobic coating obtained by the wear-resistant super-hydrophobic coating preparation method proposed by the present invention has the advantages of strong mechanical wear resistance of the body, strong coating bonding and low wear, which has never been reported. The method provided by the present invention provides a greater reference value for improving the mechanical wear resistance of the super-hydrophobic coating, and the water contact angle of the prepared super-hydrophobic coating exceeds 155°, and the water droplet rolling angle is less than or equal to 1°. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The epoxy resin used in the following embodiments of the present invention is the M83330 product provided by Myrel Corporation; the aminosilane is the M29665 product provided by Myrel Corporation; the tetraethyl orthosilicate is the M26658 product provided by Myrel Corporation; the hydroxylated-modified carbon nanotubes are the XFM02 products provided by Pioneer Nanotechnology Co., Ltd.; and the perfluorosilane is the M76117 product provided by Myrel Corporation for perfluorodecyltrimethoxysilane.

[0025] Example 1

[0026] Epoxy resin, aminosilane, tetraethyl orthosilicate and ethanol were stirred at a mass ratio of 13:10:9:70 for 30 minutes to obtain a transparent solution;

[0027] When the ethanol in the transparent solution obtained above is calibrated to 15 mL, 5 g of zinc oxide (particle size of 30 nm) and 0.15 g of hydroxylated carbon nanotubes are added to the transparent solution obtained, and stirring is continued for 30 min to obtain a mixed solution;

[0028] The mixed sol obtained above was placed in a water bath at 60°C, 1.5 g of perfluorosilane was added, stirred for 30 min, and then ultrasonically treated for 20 min to obtain an organic-inorganic long chain integrated sol;

[0029] The organic-inorganic long chain integrated sol obtained above was cast on the surface of the aluminum alloy, and after curing at 100° C. for 1 h, a wear-resistant super-hydrophobic coating was obtained.

[0030] The WS-2005 coating adhesion automatic scratch tester was used to test the binding force of the super-hydrophobic coating prepared in Example 1 of the present invention. The test result showed that the binding force of the super-hydrophobic coating was 8.5N.

[0031] The wear loss of the super-hydrophobic coating prepared in Example 1 after 1.2 m of reciprocating wear with 240# sandpaper and 750g load was only 128mg.

[0032] The water contact angle and water rolling angle of the super-hydrophobic coating prepared in Example 1 were tested using a contact angle meter. The detected water contact angle was 157° and the water rolling angle was 1°. Observation using an Olympus microscope showed that when water droplets were scattered on the surface of the super-hydrophobic coating, the water droplets could easily roll away from the surface.

[0033] Example 2

[0034] Epoxy resin, aminosilane, tetraethyl orthosilicate, and ethanol were stirred at a mass ratio of 13:10:9:75 for 30 minutes to obtain a transparent solution;

[0035] When the ethanol in the transparent solution obtained above is calibrated to 15 mL, 5 g of zinc oxide (particle size of 30 nm) and 0.15 g of hydroxylated carbon nanotubes are added to the transparent solution obtained, and stirring is continued for 30 min to obtain a mixed solution;

[0036] The mixed sol obtained above was placed in a water bath at 60° C., 2 g of perfluorosilane was added, stirred for 40 min, and then ultrasonically treated for 20 min to obtain an organic-inorganic long chain integrated sol.

[0037] The organic-inorganic long chain integrated sol obtained above was cast on the surface of the aluminum alloy, and after curing at 120° C. for 2 h, a wear-resistant super-hydrophobic coating was obtained.

[0038] According to the method of Example 1, the super-hydrophobic coating prepared in Example 2 of the present invention was tested. The test results showed that the water contact angle was 158° and the water rolling angle was 1°. When water droplets were scattered on the surface of the prepared super-hydrophobic coating, the water droplets could easily roll away from the surface.

[0039] The WS-2005 coating adhesion automatic scratch tester was used to test the binding force of the super-hydrophobic coating prepared in Example 2 of the present invention. The test result showed that the binding force of the super-hydrophobic coating was 8.4N.

[0040] The wear amount of the super-hydrophobic coating prepared in Example 2 after reciprocating wear with 240# sandpaper and a load of 750g was only 104mg after 1m.

[0041] Comparative Example 1

[0042] Epoxy resin, aminosilane, tetraethyl orthosilicate, and ethanol were stirred at a mass ratio of 13:20:9:70 for 30 minutes to obtain a transparent solution;

[0043] When the ethanol in the transparent solution is calibrated to 15 mL, 5 g of zinc oxide (particle size of 30 nm) and 0.15 g of hydroxylated carbon nanotubes are added to the transparent solution, and stirring is continued for 30 min to obtain a mixed solution;

[0044] The mixed sol obtained above was placed in a water bath at 60°C, 1.5 g of perfluorosilane was added, stirred for 30 min, and then ultrasonically treated for 20 min to obtain an organic-inorganic long chain integrated sol;

[0045] The organic-inorganic long chain integrated sol obtained above was cast on the surface of the aluminum alloy, and after curing at 100° C. for 1 hour, a wear-resistant and hydrophobic coating was obtained.

[0046] According to the method of Example 1, the hydrophobic coating prepared in Comparative Example 1 was tested, and the test results showed that the water contact angle was 122°, the water rolling angle was greater than 10°, and it did not have super hydrophobicity. The WS-2005 coating adhesion automatic scratch tester was used to test the binding force of the super hydrophobic coating prepared in Comparative Example 1 of the present invention, and the test result showed that the binding force of the super hydrophobic coating was 10.2N.

[0047] Compared with Example 1, the amount of aminosilane added in Comparative Example 1 was increased to 2 times, and the wettability and bonding strength of the coating were greatly different.

[0048] Comparative Example 2

[0049] Epoxy resin, aminosilane, tetraethyl orthosilicate, and ethanol were stirred at a mass ratio of 13:10:9:75 for 30 minutes to obtain a transparent solution;

[0050] When the ethanol in the transparent solution is calibrated to 15 mL, 3 g of zinc oxide (particle size of 30 nm) and 0.15 g of hydroxylated carbon nanotubes are added to the transparent solution, and stirring is continued for 30 min to obtain a mixed solution;

[0051] The mixed sol obtained above was placed in a water bath at 60°C, 0.2 g of perfluorosilane was added, stirred for 30 min, and then ultrasonically treated for 20 min to obtain an organic-inorganic long chain integrated sol;

[0052] The organic-inorganic long chain integrated sol obtained above was cast on the surface of the aluminum alloy, and after curing at 100° C. for 1 hour, a wear-resistant and hydrophobic coating was obtained.

[0053] According to the method of Example 1, the performance of the hydrophobic coating prepared in Comparative Example 2 was tested. The test results showed that the water contact angle was 102°, the water rolling angle was greater than 10°, and it did not have super hydrophobicity. Compared with Example 2, the amount of perfluorosilane added in Comparative Example 2 was reduced by 10 times, and the wettability of the coating was greatly different.

[0054] The WS-2005 coating adhesion automatic scratch tester was used to test the binding force of the super-hydrophobic coating prepared in Comparative Example 2 of the present invention. The test result showed that the binding force of the super-hydrophobic coating was 8.4N.

[0055] Comparative Example 3

[0056] Epoxy resin, aminosilane, tetraethyl orthosilicate, and ethanol were stirred at a mass ratio of 13:10:9:70 for 30 minutes to obtain a transparent solution;

[0057] 5 g of zinc oxide (particle size 30 nm) and 0.15 g of hydroxylated carbon nanotubes were added to 15 mL of ethanol and stirred for 30 min to obtain a mixed solution;

[0058] The mixed sol obtained above was placed in a water bath at 60° C., 1.5 g of perfluorosilane was added, stirred for 30 min, and then ultrasonically treated for 20 min. After drying, fluorinated super-hydrophobic nanoparticles were obtained.

[0059] When the ethanol in the transparent solution of the epoxy resin, aminosilane, tetraethyl orthosilicate and ethanol is calibrated to 15 mL, the fluorinated super-hydrophobic nanoparticles are added to the transparent solution, and stirring is continued for 30 minutes to obtain a mixed sol;

[0060] The mixed sol obtained above was cast on the surface of the aluminum alloy, and after curing at 100° C. for 1 h, a wear-resistant and hydrophobic coating was obtained.

[0061] According to the method of Example 1, the hydrophobic coating prepared in Comparative Example 3 was tested, and the test results showed that the water contact angle was 145°, the water rolling angle was greater than 10°, and it did not have super hydrophobicity. Compared with Example 1, the order of adding perfluorosilane in Comparative Example 3 was changed, and the wettability of the coating was greatly different.

[0062] The WS-2005 coating adhesion automatic scratch tester was used to test the binding force of the super-hydrophobic coating prepared in Comparative Example 3 of the present invention. The test result showed that the binding force of the super-hydrophobic coating was 8.5N.

[0063] Comparative Example 4

[0064] Epoxy resin, aminosilane, tetraethyl orthosilicate, and ethanol were stirred at a mass ratio of 13:10:9:70 for 30 minutes to obtain a transparent solution;

[0065] The transparent solution obtained above was placed in a water bath at 60°C, 1.5 g of perfluorosilane was added, and the stirring time was 30 min to obtain a fluorinated organic long-chain sol;

[0066] 5 g of zinc oxide (particle size 30 nm) and 0.15 g of hydroxylated carbon nanotubes were added to 15 mL of ethanol and stirred for 30 min to obtain a mixed solution;

[0067] The mixed sol obtained above was placed in a water bath at 60° C., 1.5 g of perfluorosilane was added, stirred for 30 min, and then ultrasonically treated for 20 min. After drying, fluorinated super-hydrophobic nanoparticles were obtained.

[0068] When the ethanol in the fluorinated organic long-chain sol is calibrated to 15 mL, the fluorinated super-hydrophobic nanoparticles are added and stirred for 30 min to obtain a mixed sol;

[0069] The mixed sol obtained above was cast on the surface of the aluminum alloy, and after curing at 100° C. for 1 h, a wear-resistant and hydrophobic coating was obtained.

[0070] According to the method of Example 1, the super-hydrophobic coating prepared in Comparative Example 4 was tested. The test results showed that the water contact angle was 155°, the water rolling angle was greater than 4°, and it had super-hydrophobicity but the water droplet rolling angle was high.

[0071] The WS-2005 coating adhesion automatic scratch tester was used to test the binding force of the super-hydrophobic coating prepared in Comparative Example 4 of the present invention. The test result showed that the binding force of the super-hydrophobic coating was 7N.

[0072] Compared with Example 1, the perfluorosilane in Comparative Example 4 was modified in two steps instead of one step, and the wettability and bonding strength of the coating were greatly different.

[0073] The invention provides a method for preparing a wear-resistant super-hydrophobic coating. A fluorinated organic-inorganic long-chain integrated sol is first prepared. The super-hydrophobic coating obtained after curing has the advantages of mechanical wear resistance, strong coating bonding force and low wear amount. In the invention, the mass ratio of tetraethyl orthosilicate and aminosilane in the sol determines the wear resistance and surface wettability of the super-hydrophobic coating. The mass ratio of metal oxide and hydroxylated modified carbon nanotube has a great influence on the bonding force and mechanical wear resistance of the super-hydrophobic coating. The modification process of fluorosilane not only improves the water drop contact angle of the resin material, but also improves the water drop contact angle of the nano filler. A reasonable fluorosilane addition concentration is very important to reduce the water drop rolling angle of the wear-resistant super-hydrophobic coating.

[0074] The invention provides a method for preparing a wear-resistant super-hydrophobic coating, which has strong bonding force between the coating and a substrate and excellent mechanical wear resistance. The method can be applied to various substrate surfaces to obtain super-hydrophobic properties, and has application prospects in many fields such as construction, machinery manufacturing, aerospace, and navigation. The super-hydrophobic coating prepared by the invention has strong hydrophobicity, a water drop contact angle greater than 155°, and a rolling angle less than or equal to 1°. The super-hydrophobic coating is solidified based on a sol-gel that integrates organic-inorganic long chains, and provides a greater reference value for improving the mechanical wear resistance of the super-hydrophobic coating.

[0075] Although the present invention has been described and illustrated with reference to specific embodiments of the present invention, these descriptions and illustrations do not limit the present invention. It will be clearly understood by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention as defined by the appended claims, so that specific circumstances, materials, material compositions, materials, methods or processes are suitable for the goals, spirit and scope of the present application. All such modifications are intended to be within the scope of the appended claims. Although the methods disclosed herein have been described with reference to specific operations performed in a specific order, it should be understood that these operations may be combined, subdivided or reordered to form equivalent methods without departing from the teachings of the present invention. Therefore, unless specifically indicated herein, the order and grouping of operations are not limitations of the present application.

Claims

1. A method for preparing a wear-resistant super-hydrophobic coating, comprising: The epoxy resin, aminosilane, tetraethyl orthosilicate and ethanol are first mixed to obtain a solution; The solution is mixed with metal oxide and carbon nanotubes for a second time to obtain a mixed solution; The mixed solution and fluorosilane are mixed for the third time to obtain a sol; The sol is solidified to obtain a wear-resistant super-hydrophobic coating.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the epoxy resin, aminosilane, tetraethyl orthosilicate and ethanol is selected from 13:10:9:(65-75).

3. The preparation method according to claim 1, characterized in that: The particle size of the metal oxide is selected from 25 to 35 nm.

4. The preparation method according to claim 1, characterized in that: The metal oxide is selected from one or more of silicon dioxide, titanium dioxide and zinc oxide.

5. The preparation method according to claim 1, characterized in that: The carbon nanotubes are selected from hydroxylated carbon nanotubes.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the metal oxide to the carbon nanotube is selected from 100:

3.

7. The preparation method according to claim 1, characterized in that: The concentration of the metal oxide in ethanol is selected from (0.25-0.4) g / mL.

8. The preparation method according to claim 1, characterized in that: The concentration of the fluorosilane in ethanol is selected from (0.1 to 0.2) g / mL.

9. The preparation method according to claim 1, characterized in that: The temperature of the third mixing is selected from 50 to 70°C.

10. The preparation method according to claim 1, characterized in that: The curing temperature is selected from 90 to 120°C.

Citation Information

Patent Citations

  • Preparation method of stable superhydrophobic hot liquid coating

    CN105440888A

  • Wear-resistant super-hydrophobic coating compound

    CN106634064A

  • Preparation and application of super-hydrophobic / oleophobic coating layer with excellent performance

    CN111019482A